The Influence of Flashcard on Arabic Learning Outcomes of Shorof Subject for Junior High School Students - Siregar, Amy Fitriani; Firdaus, Ananda Zalfa; Setiyawan, Agung; Wulandari, Dina Ayu; Putri Damayanti, Lutvi Yunita; Syifaaussakinah, Syifaaussakinah (Universitas Islam Negeri Raden Intan Lampung, 2024)
Difficulties in learning Shorof for students are frequently found but the innovation of learning media utilization in this subject is quite rare. The article analyzed about how effective the use of flashcards media on Shorof subjects to support the quality of learning for junior high school students. The research was conducted with experimental quantitative methods, and the research design was a true experiment. The experimental class and the control class were chosen randomly in order to that students' abilities were equal. The samples of learning outcomes were obtained from 15 students who were randomly selected from the experimental and control classes with a total sample of 30 students. In collecting data, the tests and documentation were used, whereas data analysis was carried out with SPSS 26 through the Mann-Whitney non-parametric test because the data were normally distributed and not homogeneous. From this research, it was concluded that there were differences in the learning outcomes of the experimental and control classes after the treatment, which the experimental class got higher score than the control class with an average score of 93.3327:62.0520, which means that there was a positive impact of using flashcards on student learning outcomes evidenced by the Mann Whitney test of 0.000 < 0.05. Based on the valid test results, it was suggested that Shorof flashcards can be used in various institutions as Shorof learning subject in general to increase the learning methods more creative and innovative.